Lipid biomarkers as pH proxies of sediment core NGBA19 - Valentine Schaaff; Vincent Grossi; Matthew Makou; Yannick Garcin; Pierre Deschamps; David Sebag; Benjamin Ngounou Ngatcha; Guillemette Ménot (PANGAEA, 2024)
Here, we present data on lipid biomarkers (branched glycerol dialkyl glycerol tetraethers (brGDGTs) and hopanes) from the NGaoundaba peat deposit (NE Cameroon - Adamawa Plateau - N7.135° E13.690°) spanning the last 10 ka. The data comprise concentrations of hopanes, C31 hopane carbon isotopic composition (when available), hopane isomer ratio and CBTpeat ratio as well as pH reconstructions based on empirical calibration from Naafs et al. 2017 and Inglis et al. 2018. The core was collected on February 2019 and named NBGA19. The 6-meter-long core was sub-sampled at 2.5-cm intervals. 73 samples were analyses. Lipid biomarkers were extracted using MARS 6 CEM microwave extraction system and then separated by column chromatography on silica gel into three fractions. Data were obtained using HPLC-APCI-MS (Agilent 1200) (LGL-TPE, ENS de Lyon, France) or GC-MS (Agilent) and GC-IRMS (Agilent 9870B GC coupled to an isoprime visION IRMS via an isopirme GC-5 combustion interface Elementar) (LGL-TPE Université Claude Bernard Lyon 1, France). Carbon isotopic compositions was calibrated using a reference CO2 gas reported to VPDB scale.